An add-on damping enhancement with adjustable gain for lightly damped system. (15th May 2023) - Li, Jiedong; Sun, Mingwei; Chen, Zengqiang
Abstract: The inherently difficult problem with very lightly damped systems is the extreme sensitivity at the resonance peaks, which results in severe performance degradation even for small model uncertainty. And it is also difficult to cancel the undesirable lightly damped poles from different sensitivity functions. To this end, this paper presents an add-on damping compensation approach with adjustable gain, which can handle uncertain resonance frequency and effectively improve the vibration suppression performance in terms of different sensitivity functions. First, the lightly damped model is included in the observer form by augmenting the system with two extra state variables, which can simultaneously estimate the total disturbance and the resonance mode via prior resonance knowledge. Second, the add-on damping compensation term is applied to improve the vibration suppression performance. Third, the parameters tuning guideline is thereby provided via the frequency domain analysis. Several simulations and experiments are successfully implemented in the established two-mass–spring (TMS) system, and the results validate the effectiveness and superiority of the proposed method. Graphical abstract: Highlights: The add-on damping compensation term with adjustable gain is designed. Only one tunable parameter is introduced as an additional degree of freedom. The superiority of the proposed method are verified by simulations and experiments.